First record of Chilomima clarkei (Amsel) (Lepidoptera: Crambidae) in Manihot esculenta Crantz (Euphorbiaceae) in Amapá state, Brazil - Adaime, Ricardo; Santos, Rodrigo Souza; Lopes Lima, Adilson; Emille Veloso dos Santos, Jhulie; Specht, Alexandre (EntomoBrasilis, 2020)
The present study reports Chilomima clarkei (Amsel) (Lepidoptera: Crambidae) infesting stems of Manihot esculenta Crantz (Euphorbiaceae) in Amapá state, Brazil, for the first time. Considering the importance of this species as a pest, it is necessary to publicize its occurrence and provide information about the main symptoms of the attacked plants and morphological characters of development stages to identify it quickly in crops. As there are no registered products for this pest's control, producers are advised to pay attention to any sign of infestation. To avoid it from spreading, they are also recommended to remove and burn all the infested parts detected in the plantations, in addition to selecting healthy manivas (stem cuttings) at the time of replanting, preventing the infestation of new crops.